Marketable and Marketed Surplus of Rice and Wheat in India: Distribution and Determinants - Vijay Paul Sharma (Ind. Jn. of Agri. Econ., 2016)
Over the last few decades, Indian agriculture has witnessed significant changes and become market-oriented due to changing policies, dietary diversification, urbanization, population growth, technological changes, infrastructure and expanding exports opportunities. Farm households, who allocated a significant portion of their resources to foodgrains production largely for self-consumption, produce increasingly for the market. The present study was undertaken to assess the marketed and marketable surplus of rice and wheat, major cereals, in leading producing states and examine important factors, which determine the level of marketed surplus on various categories of farm households. These trends clearly indicate that the government has almost a monopsony in rice and wheat procurement and restricted the participation of private sector. The results of marketed surplus show that about 78 per cent of total rice production was sold in the market and varied from about 63 per cent on marginal farms to about 81 per cent on medium and larger farms.